2013
DOI: 10.1245/s10434-013-3134-z
|View full text |Cite
|
Sign up to set email alerts
|

Robotic Versus Laparoscopic Adrenalectomy for Pheochromocytoma

Abstract: To our knowledge, this is the first study comparing robotic versus laparoscopic resection of pheochromocytoma. Our results show that the robotic approach is similar to the laparoscopic regarding safety and efficacy. The lower morbidity, less immediate postoperative pain, and shorter hospital stay observed in the robotic approach warrant further investigation in future larger studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
70
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 88 publications
(75 citation statements)
references
References 19 publications
5
70
0
Order By: Relevance
“…Most of these studies have been retrospective observational comparative studies, 13,14,[16][17][18][19][20][21][22][23][24]26 and only one of them was a randomized controlled trial. 15 One of the first series comparing LA with robotic adrenalectomy was by Morino et al who evaluated outcomes in 10 patients who underwent laparoscopic and robotic adrenalectomy.…”
Section: Ra Vs Lamentioning
confidence: 99%
See 1 more Smart Citation
“…Most of these studies have been retrospective observational comparative studies, 13,14,[16][17][18][19][20][21][22][23][24]26 and only one of them was a randomized controlled trial. 15 One of the first series comparing LA with robotic adrenalectomy was by Morino et al who evaluated outcomes in 10 patients who underwent laparoscopic and robotic adrenalectomy.…”
Section: Ra Vs Lamentioning
confidence: 99%
“…Patients in robotic group had a shorter OR time (149 vs 178 minutes), less EBL (36 vs 43 mL), fewer conversions (1 vs 3) and shorter LOS (1.2 vs 1.7 days). 19 Agcaoglu et al performed a prospective comparative study of 24 patients in robotic group with 38 patients in laparoscopic group undergoing adrenalectomy for large tumors (mean size: 6.5 ± 0. …”
mentioning
confidence: 99%
“…No intraoperative hypertension or other anesthetic complications were noted. The successful use of robotic partial nephrectomy in this case demonstrates that this method is as useful in the management of renal paragangliomas as it is in the management of adrenal pheochromocytomas [18]. The patient's postoperative course was free of complications and imaging studies did not show any recurrence or metastasis during a follow-up period of six months [18, 19].…”
Section: Discussionmentioning
confidence: 95%
“…Recent data have shown that robotic resection is a non-inferior technique regarding safety and efficacy. 4 Similarly, concerning paraganglioma surgery, the mini-invasive laparoscopic approach is the current treatment of choice. Goers and colleagues 5 reported a safety profile with low morbidity and outcome similar to adrenal pheochromocytomas; conversely in this series performed through lateral transperitoneal approach, the surgical time was significantly longer.…”
Section: Discussionmentioning
confidence: 99%